Expression and purification of antimicrobial peptide AP2 using SUMO fusion partner technology in Escherichia coli. (1st December 2018) - Mo, Q.; Fu, A.; Lin, Z.; Wang, W.; Gong, L.; Li, W.
Abstract : Abstract: Apidaecins (APs) are proline‐rich antimicrobial peptides that were isolated from Apismelifera . APs possess broad‐spectrum activities against Gram‐negative bacteria and exhibit immune‐modulatory functions. AP2, an artificial mutant AP peptide with improved activities, was expressed in Escherichia coli expression system using small ubiquitin‐related modifier (SUMO) fusion technology and ZYM‐5052 auto‐induction medium. Approximately 23 mg of recombinant fusion protein smt3AP2 was purified per litre cultivated medium. After SUMO protease (Ulp) cleavage of smt3AP2, recombinant AP2 was further purified by affinity and cation exchange chromatography. The pure recombinant AP2 with calculated value of 2·23 kDa reached a yield of 2·7 mg l −1 and exhibited powerful antibacterial activity towards E. coli K88 with minimum inhibitory concentration at 5 μ g ml −1 . The recombinant fusion strategy presented in this study allows convenient high yield and easy purification of recombinant AP2. Significance and Impact of the Study: AP2, an artificial mutant apidaecin (AP) peptide based on APs, has improved activities and may be regarded as a promising antibiotic alternatives. The secreted expression of antimicrobial peptide is of the greatest challenges because the antibacterial activity is not beneficial to the host. Our data suggest that the recombinant fusion strategy allows convenient high yield and easy purification of recombinant AP2.